Identifikasi Kesesuaian Kawasan Wisata Panatai Saleo Kecamatan Waigeo Selatan Kampung Saonek Kabupaten Raja Ammpat - Husen Humalelen; Abd Malik; M Nur Zakaria Leo (UNM Geographic Journal, 2020)
This study aims 1) to find out how the Ecological land condition of the Tourism area in Saleo Beach, South Waigeo District, Saonek Village, Raja Ampat Regency. 2) to find out the shape of the tourist area in Saleo Beach, South Waigeo District, Saonek Village, Raja Ampat Regency. Data collection is done by interviewing techniques and documentation. The analysis technique used is qualitative descriptive analysis. The results showed: Physical condition of Saleo Beach The physical condition at Saleo beach is the highest tide of 1.58cm. And the average tidal range obtained is 0.95 m. The average wave height ranges from 0.08m-0.43m. with a current speed of 0.2m / s. With 100% water brightness with a depth of 350 cm and water temperature range of 27 ̊ -29 ̊ C, the depth of the Saleo coast 0-25 m. slope drought has a flat condition. So that the value of the physical parameters of Saleo beach as much as 85.71% is in the range obtained from 90 -100% into the category of very feasible (S). infrastructure and accessibility. In this case it is still lacking the comfort conditions for visitors who come and even though there are places to stay and some places to relax or rest on the beach. Thus the feasibility of Saleo Beach is included in the quite feasible category with the feasibility value.